DNA sequence and transcript mapping of a soybean gene encoding a small heat shock protein - Czarnecka, Eva (1985)
The DNA sequence of a gene (Gmhsp17.5-E) encoding a small heat shock protein of soybean, Glycine max, has been determined. Nuclease S1 mapping of the 5′ terminus of the corresponding RNA indicates that the start site for transcription is located 82 bases upstream from the coding region and 24 bases downstream from a “TATA”-like region (-T-T-T-A-A-A-T-A-). The 5′ flanking region of Gmhsp17.5-E contains two imperfect dyads that closely resemble regulatory elements present in the promoters of heat-inducible genes of Drosophila. One, positioned 18 bases upstream from the TATA-like region, shows 90% homology to the Drosophila heat shock consensus sequence. The other overlaps an upstream TATA sequence and is located at position -213. Analysis of the derived amino acid sequence indicates that the protein encoded by Gmhsp17.5-E is related structurally to the four small heat shock proteins of Drosophila. This relationship is most evident by comparison of hydropathy profiles; they show conservation of several major hydrophilic and hydrophobic regions, which suggests that these proteins have common structural features.